Concessional urbanism. Modernization, privatization and hegemony change in urban action (Ciudades, 2017)
This article discusses one of the most illustrious manifestations of neoliberalism in its application to the construction of the city: urban development concession. In order to do this, first we shall turn into the emergence of neoliberalism, its political, economic and ideological roots, and then we shall study its application to the urban field. We will see how the neoliberal urbanism strives to replace the urbanism consolidated mainly after World War II, the so-called reformist urbanism, and we will focus on one of its most powerful tools, the urban concession (grants or allowances). Our field of reflections is limited on the Spanish case. We shall highlight how, in the confrontation to conquer a hegemonic position in the real estate and construction market, there are two groups with opposed interests, those of the agrarian land owners confronted with those of the lobby of the promoters, who have strong links and dependence on financial capital. We shall take account of the advances and setbacks in this conflict, although the positions of the latter ones seem to be gaining ground, especially with the approval of the Rehabilitation, Regeneration and Renewal Urban Act in 2013.
Keywords: neoliberalism; reformist urbanism; neoliberal urbanism; appropriation of urban capital gains (surplus); urban development concession (awards or grants)